Konstitusionalitas Perlindungan Data Pribadi sebagai Bagian dari Hak atas Rasa Aman - Mardiyati, Siti (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
Personal data protection in the digital age is not merely a technical issue, but a constitutional right rooted in the guarantee of security in the 1945 Constitution, particularly Articles 28G, 28D, and 28I. This study uses a normative juridical approach to examine the position of the right to personal data within the constitutional framework. The results of the study confirm that data misuse or leakage is not only technically detrimental, but also violates human rights and neglects the obligations of the state. From a humanistic perspective, this protection determines the level of public trust when engaging in activities in the digital space. Therefore, the existence of the 2022 Personal Data Protection Law must be followed by consistent law enforcement, the establishment of an independent authority, and increased digital literacy. Thus, the constitutionality of personal data protection strengthens the state's role in maintaining the dignity of citizens while creating a sense of security in everyday life.